Early Bunyavirus-host cell interactions - Albornoz, Amelina; Hoffmann, Anja; Lozach, Pierre-Yves (Viruses, 2016)
The Bunyaviridae is the largest family of RNA viruses, with over 350 members worldwide. Several of these viruses cause severe diseases in livestock and humans. With an increasing number and frequency of outbreaks, bunyaviruses represent a growing threat to public health and agricultural productivity globally. Yet, the receptors, cellular factors and endocytic pathways used by these emerging pathogens to infect cells remain largely uncharacterized. The focus of this review is on the early steps of bunyavirus infection, from virus binding to penetration from endosomes. We address current knowledge and advances for members from each genus in the Bunyaviridae family regarding virus receptors, uptake, intracellular trafficking and fusion.
Gesehen am 17.09.2019